2020
DOI: 10.1084/jem.20200866
|View full text |Cite
|
Sign up to set email alerts
|

Exit from germinal center to become quiescent memory B cells depends on metabolic reprograming and provision of a survival signal

Abstract: A still unanswered question is what drives the small fraction of activated germinal center (GC) B cells to become long-lived quiescent memory B cells. We found here that a small population of GC-derived CD38intBcl6hi/intEfnb1+ cells with lower mTORC1 activity favored the memory B cell fate. Constitutively high mTORC1 activity led to defects in formation of the CD38intBcl6hi/intEfnb1+ cells; conversely, decreasing mTORC1 activity resulted in relative enrichment of this memory-prone population over the recycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 52 publications
1
53
1
Order By: Relevance
“…Immunization of mice harboring B cell-specific deletion of Prkaa1 with a T-dependent antigen revealed that AMPK initially dampens the generation of B cells harboring MBC surface markers when screening at a time coincident with the peak of the GC response in vivo [ 20 ]. On the surface, this finding differs from recent evidence that the GC B cell to MBC transition is facilitated by relatively lower mTORC1 activity in GC B cells [ 30 ]. In contrast to its role in dampening the initial population numbers of MBC, AMPK supports the long-term maintenance of the MBC population: numbers of Prkaa1 -deficient MBC were diminished compared to wild-type controls several weeks after the peak of the GC response [ 20 ].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Immunization of mice harboring B cell-specific deletion of Prkaa1 with a T-dependent antigen revealed that AMPK initially dampens the generation of B cells harboring MBC surface markers when screening at a time coincident with the peak of the GC response in vivo [ 20 ]. On the surface, this finding differs from recent evidence that the GC B cell to MBC transition is facilitated by relatively lower mTORC1 activity in GC B cells [ 30 ]. In contrast to its role in dampening the initial population numbers of MBC, AMPK supports the long-term maintenance of the MBC population: numbers of Prkaa1 -deficient MBC were diminished compared to wild-type controls several weeks after the peak of the GC response [ 20 ].…”
contrasting
confidence: 99%
“…As noted, AMPK is a negative regulator of mechanistic target of rapamycin complex 1 (mTORC1), a multi-subunit complex that promotes protein synthesis. mTORC1 and likely the dynamic regulation of its activity are critical for affecting outcomes of both germinal center and extra-follicular responses [ 27 30 ]. Loss of Prkaa1 in B cells led to elevated mTORC1 activity in vivo and after in vitro activation [ 20 , 31 ].…”
mentioning
confidence: 99%
“…The memory B cell compartment serves as an immune reservoir that contains a diverse collection of antibodies 13,14 . To enumerate RBD-specific memory B cells, we performed flow cytometry using a biotin-labeled RBD 3 (Fig.…”
Section: Memory B Cellsmentioning
confidence: 99%
“…In addition to driving affinity maturation, the GC selects for differentiation into both PCs and MBCs. Precursors of these populations must exist in the GC and, indeed, some have been identified ( 16 , 44 , 45 ). However, these populations are not observed upon simple division of the GC into two populations.…”
Section: Gc Cellular Evolutionmentioning
confidence: 99%
“…In contrast MBCs develop from low-affinity B cell clones that receive low strength signals from T FH ( 5 , 86 88 ). Weak T cell help also results in low Myc and mTORC1 activation, which also predisposes to differentiation into MBCs ( 44 ). Overall, these studies indicate that high affinity BCRs and strong T FH interactions predispose to PC differentiation while low affinity BCRs, and poor T cell help, leads to differentiation into MBCs.…”
Section: Gc Cellular Evolutionmentioning
confidence: 99%